Corporate social capital, market orientation, organizational learning and service innovation performance: An empirical survey in the Pearl River Delta of China - Zhaoquan Jian; Yulu Zhou (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Service innovation performance (SIP) is an important driver of growth and wealth of service firms in wide range of industries. Yet, few research studies have been done to explore the influencing factors. The purpose of this study intends to identify the impacts of corporate social capital, market orientation and organizational learning on service innovation in the Pearl River Delta of China. Design/methodology/approach: The paper mainly adopted the empirical research. A Structure Equation Model containing an intermediary variable was established to explore the relationships of SIP. Findings and Originality/value: The main findings of the research support some of the propositions: (1) Both corporate social capital, market orientation and organizational learning have distinct positive impact on service innovation performance; (2) Corporate social capital, market orientation has a positive effect on organizational learning respectively, and (3) organizational learning plays a mediating role between the corporate social capital, market orientation and service innovation performance. Research limitations/implications: The research object of this paper has been restricted to the enterprises in Pearl River Delta of China. By contrast, variables and theories all come from western research, which was not adequate in explaining some results in the context of China. Given the limited theoretical and empirical research to service innovation, future research studies might widen their examinations to include other potential factors. Practical implications: This study has significant implications to enterprises. The results of this study suggest that enterprises should establish the social networks accommodated by the development of organization. In addition, more attention should be paid to focus on market orientation to enhance the ability to respond to changes in the market environment. It's particularly necessary to strengthen organizational learning to improve the ability of information. Originality/value: The insights from this paper can help service managers to better understand the relationship among corporate social capital, market orientation, organizational learning and service innovation performance in the context of China's economic transformation, as well as provide some useful guidance for the service sector's innovation activities.
Keywords: 650; Corporate Social Capital (CSC); Market Orientation (MO); Organizational Learning (OL); Service Innovation Performance (SIP)